Faktor Pribadi dan Faktor Psikologis yang Memengaruhi Perilaku Konsumen dalam Pembelian Songket di Toko Mawar Songket - Tiara Veranica; M. Syahirman Yusi; A. Jalaluddin Sayuti (Jurnal Aplikasi Manajemen dan Bisnis, 2022)
The purpose of this study was to analyze the most dominant personal and psychological factors in influencing consumer behavior in purchasing songket at Mawar Songket store and how much these factors affected consumer behavior in purchasing songket at Mawar Songket store. Problem solving was done by quantitative-descriptive research method with a technique in the form of a survey of consumers of the Mawar Songket store through a questionnaire. The data in this study used analysis of instrument test, multiple linear regression tests with partial and simultaneous tests which were processed with IBM SPSS version 25. From the results of the study, it was concluded that personal factors did not significantly influence consumer behavior. While psychological factors had a significant effect on consumer behavior at Mawar Songket store. Psychological factors gave the most dominant influence on consumer behavior at Mawar Songket store. Enhancement in songket types and prices need to be strengthened in order to encourage consumers' personal factors in purchasing songket at Mawar Songket store based on consumer behavior.